The Effect of Using Robopong, Spinwheel, and Return Board on The Accuracy of Top Spin Strikes - Moh Ginanjar Sahuri; Tatang Muhtar; Indra Safari; Anggi Setia Lengkana (Journal of Physical Education Health and Sport, 2026)
Top spin is an important technique in table tennis that requires targeted training with the right media, but the effectiveness of various training media such as robopong, spinwheel, and return board in improving top spin accuracy has not been studied much comparatively. The purpose of this study was to determine the effectiveness of the influence provided by the media or training tools (robopong, spinwheel and return board) on improving the accuracy of top spin strokes in table tennis. The research method used in this study is Quasi-Experimental Design: Pretest–Posttest Nonequivalent Groups Design, where the sample will be divided into three groups by starting with pretest data collection then treatment in groups for 12 meetings and ending with a posttest. The sample consisted of 15 active members of the Table Tennis Student Activity Units  UPI Sumedang Campus, the sample selection was carried out using a purposive sampling technique which was then continued with a group division technique using the Matching-Only Design technique. The results of the study showed that there was a significant influence of the three media or training tools on improving the accuracy of top spin strokes in table tennis, however, the post-hoc test showed no significant difference between the three training media on improving the accuracy of top spin strokes in table tennis. So it can be concluded that the three training media have an effect on increasing the accuracy of top spin strokes in table tennis, but there is no significant difference. The three research groups have a relatively similar level in increasing the accuracy of top spin strokes, although the average for each group is different, but it is not enough to show significant effectiveness in influencing the accuracy of top spin in the sport of table tennis.